Perpetrators of intimate femicide : a study of forensic records - Mayer, Victoria (2006)
Includes bibliographical references (leaves 90-96).Intimate femicide is prevalent in South Africa, and represents the lethal end of a continuum of male perpetrated intimate partner violence. For various reasons attention has only begun to be paid to intimate femicide in the last three decades. International research has established existing rates for intimate femicide, mostly in North America and the United Kingdom, and has confirmed that intimate femicide constitutes a unique form of homicide, which does not fit with the established patterns for other forms of homicide. South African studies have predominantly focused on establishing the rate of intimate femicide in the country. This study sought to examine a smaller number of intimate femicides (n=24) within a broader context in order to provide information, not only on the perpetrator and the victim, but also the state and status of their relationship, and to investigate how the perpetrator accounts for the event